The Toad Sleeps Over - John Bianchi (New York Bungalo Books)
When Tony the toad comes for an overnight stay, the Mouse family discovers how different the two kinds of animals are, but also the advantages of having a toad for a friend, especially when they meet a coyote.
Keywords: Read Aloud -- Read Aloud